2020
DOI: 10.3389/fcomm.2020.602471
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Situational Word Learning in Two Foreign Languages: Effects of Native Language and Perceptual Difficulty

Abstract: Cross-situational word learning (CSWL) paradigms have gained traction in recent years as a way to examine word learning in ambiguous scenarios in infancy, childhood, and adulthood. However, no study thus far has examined how CSWL paradigms may provide viable learning pathways for second language (L2) word learning. Here, we used a CSWL paradigm to examine how native Australian English (AusE) speakers learned novel Dutch (Experiment 1) and Brazilian Portuguese (Experiment 2) word-object pairings. During each le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Since object-word correspondences are not made explicit, the word-referent pairings can only be inferred across trials and therefore occurs through SL (Mulak et al, 2019). A multitude of studies have used CSWL tasks to demonstrate cross-situational learning for different types of language learners, such as infants (Escudero et al, 2016b;Smith & Yu, 2008), children (Suanda, et al, 2014) and adults (Escudero et al, 2016;Escudero et al, 2016a;Yu & Smith, 2007), bilinguals (Escudero et al, 2016), non-native listeners (Tuninetti et al, 2020), and across differing degrees of referential ambiguity (Mulak et al, 2019). It has also been shown that phonological coding ability affects CSWL efficiency (Escudero et al, 2016;Mulak et al, 2019) and that mappings are retained over time (Vlach & Sandhofer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since object-word correspondences are not made explicit, the word-referent pairings can only be inferred across trials and therefore occurs through SL (Mulak et al, 2019). A multitude of studies have used CSWL tasks to demonstrate cross-situational learning for different types of language learners, such as infants (Escudero et al, 2016b;Smith & Yu, 2008), children (Suanda, et al, 2014) and adults (Escudero et al, 2016;Escudero et al, 2016a;Yu & Smith, 2007), bilinguals (Escudero et al, 2016), non-native listeners (Tuninetti et al, 2020), and across differing degrees of referential ambiguity (Mulak et al, 2019). It has also been shown that phonological coding ability affects CSWL efficiency (Escudero et al, 2016;Mulak et al, 2019) and that mappings are retained over time (Vlach & Sandhofer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When hearing an unknown word outside of a teaching context, it is not always clear what the referent of that word is. Cross-situational word learning paradigms test our ability to learn words in ambiguous scenarios (e.g., [ 31 , 32 , 36 ]). These paradigms begin with an ambiguous learning phase, in which more than one referent and/or auditory word is presented in each trial.…”
Section: Experiments 1: Explicit Vs Cross-situational Word Learningmentioning
confidence: 99%
“…Research into XSWL supports it as a viable mechanism for learning words in the real world. Adults (e.g., [ 32 ]), young children (e.g., [ 37 ]), and non-native learners [ 36 ] can learn words via XSWL in the lab, even when words only differ by a single consonant or vowel [ 31 , 38 ], and adults can retain these mappings over time [ 39 ]. In a direct comparison between explicit word learning and XSWL, participants who learned words via explicit presentation were more accurate at test compared to those who learned them via XSWL, though word learning for all groups was above chance [ 35 ].…”
Section: Experiments 1: Explicit Vs Cross-situational Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of classroom practice, perception training should include a key role for explicit instruction where "learners' attention must be explicitly drawn to the differences in the L2 and the L1 via form-focused instruction (FFI), and errors in the learners' L2 production would benefit from explicit corrective feedback" (Lee et al, 2020, p.3). However, other studies have shown that methods that rely on "implicit" or "ambiguous" learning without corrective feedback also result in significant phonetic learning at the segmental and word levels (Wanrooij et al, 2013;Escudero and Williams, 2014;Ong et al, 2017;Tuninetti et al, 2020), although for very difficult L2 contrasts, "attentive" listening (with a task that draws attention to auditory stimuli), rather than "passive" (with no task performed while listening to an array of sounds), yields better results (Ong et al, 2015). In our proposal for perception-based L2 Spanish pronunciation activities (Production of Spanish /a e o/ section), we suggest using explicit and implicit methods that emphasize the important role of both prosody and contextualized speech, as per our next two design principles.…”
Section: The Importance Of Perception-focused Instructionmentioning
confidence: 99%